Callus induction and transcriptomic analysis of in vitro embryos at different developmental stages of peony - Zhu, Xiangtao; Zhu, Huijun; Ji, Wen; Hong, Erman; Lu, Zeyun; Li, Bole; Chen, Xia (Frontiers in Plant Science, 2022)
The efficient induction of peony embryogenic callus is of great significance to the improvement and establishment of its regeneration technology system. In this study, the in vitro embryos of 'Fengdanbai' at different developmental stages were selected as explants, the effects of different concentrations and types of plant growth regulator combinations on the induction and proliferation of embryonic callus at different developmental stages were investigated, and comparative transcriptome analysis of callus with different differentiation potentials were performed to explore the molecular mechanisms affecting callus differentiation. The results showed that the germination rate of 90d seed embryo was the best, which was 94.17%; the 70d and 80d cotyledon callus induction effect was the best, both reaching 100%, but the 80d callus proliferation rate was higher, the proliferation rate reached 5.31, and the optimal induction medium was MS+0.1 mg·L–1NAA+0.3 mg·L–1TDZ+3 mg·L–12,4-D, the callus proliferation multiple was 4.77. Based on the comparative transcriptomic analysis, we identified 3470 differentially expressed genes (DEGs) in the callus with high differentiation rate and low differentiation rate, including 1767 up-regulated genes and 1703 down-regulated genes. Pathway enrichment analysis showed that the "Phenylpropanoid biosynthesis" metabolic pathway was significantly enriched, which is associated with promoting further development of callus shoots and roots. This study can provide reference for genetic improvement and the improvement of regeneration technology system of peony.